Optimization of non-specific immune parameters, growth, and survival rate of Nile tilapia (Oreochromis niloticus) fingerlings using Padina sp. extract as an immunostimulant - Nurfitri Rahim; Risfany Risfany; Paletuno Soloweno; Guntur Benotirto Samudro (Acta Aquatica: Aquatic Sciences Journal, 2026)
This study aimed to evaluate the effectiveness of the macroalgae extract Padina sp. as a natural immunostimulant agent to enhance growth performance and non-specific immune responses in Nile tilapia (Oreochromis niloticus). The experiment employed a Completely Randomized Design (CRD) consisting of four treatment levels with three replications, including a control diet (without supplementation) and diets supplemented with Padina sp. extract at concentrations of 1.0 g/kg, 1.5 g/kg, and 2.0 g/kg feed. During a 14-day rearing period, Nile tilapia fingerlings measuring 5–7 cm were evaluated for hematological parameters, including total leukocyte count, erythrocyte count, leukocyte differentiation, phagocytic activity, specific growth rate (SGR), feed utilization efficiency, survival rate (SR), and water quality parameters. The best performance was observed in fish fed 1.5 g/kg Padina sp. extract, which resulted in a total leukocyte count of 8.66±2.61×10⁵ cells/mm³, lymphocyte percentage of 73±3.01%, and the highest survival rate of 93±5.44%. Water quality parameters remained within optimal ranges throughout the study, with temperature ranging from 28.5–29.5°C, pH 6.9–7.4, and dissolved oxygen levels of 5.3–5.9 ppm. Based on these findings, dietary supplementation of Padina sp. extract at 1.5 g/kg feed is considered effective as a natural immunostimulant to support sustainable Nile tilapia aquaculture. Keywords: Growth Performance; Immunostimulant; Nile Tilapia; Non-Specific Immunity; Padina sp.